2018
DOI: 10.4103/ijmr.ijmr_1517_16
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in beta-haemolytic streptococci in India

Abstract: Background & objectives:The incidence and severity of invasive and non-invasive infections demonstrate variability over time. The emerging resistance of Group A streptococci (GAS) to commonly used antibiotics is of grave concern. This study was conducted to assess the antimicrobial resistance of beta-haemolytic streptococci (βHS) in India and to ascertain the molecular mechanisms of resistance.Methods:All isolates of βHS from the Trauma Centre of All India Institute of Medical Sciences (AIIMS) (north India), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…GAS causes a wide spectrum of clinical diseases ranging from mild pharyngitis to life-threatening invasive infections ( Carapetis et al, 2005 ; Walker et al, 2014 ). Although antibiotics are effective and widely used for treating GAS infections, antibiotic resistance, especially to macrolides, is increasing in several countries ( Lu et al, 2017 ; Bhardwaj et al, 2018 ). The rise of antibiotic resistance leads to an increase in mortality, which has become a public health issue of global concern ( Wajima et al, 2014 ; Silva-Costa et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…GAS causes a wide spectrum of clinical diseases ranging from mild pharyngitis to life-threatening invasive infections ( Carapetis et al, 2005 ; Walker et al, 2014 ). Although antibiotics are effective and widely used for treating GAS infections, antibiotic resistance, especially to macrolides, is increasing in several countries ( Lu et al, 2017 ; Bhardwaj et al, 2018 ). The rise of antibiotic resistance leads to an increase in mortality, which has become a public health issue of global concern ( Wajima et al, 2014 ; Silva-Costa et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that 28% of Enterococcus species were isolated from urine samples. Different studies from different areas too concluded that urine was the most common sample yielding Enterococci, such as the studies by Mathur et al [ 23 ], Karmarkar et al [ 18 ], and Udo et al [ 24 ], who reported rates of 49%, 50%, and 37% respectively. Vancomycin and teicoplanin resistance were detected in 6.7% and 4.87% of the isolates in the current investigation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…23 Despite guidelines recommending the use of erythromycin in GABHS pharyngitis, GABHS isolates in Indian patients are found to be resistant to this antibiotic. 10,34 The minimum inhibitory concentrations (MICs) of various antibiotics against GABHS show that penicillin is the most sensitive antibiotic against GABHS (Table 6).…”
Section: Comparison Of Penicillin With Other Antibiotics In the Treat...mentioning
confidence: 99%